Research progress of the gut-microbiome-skin axis and psoriasis - Zhi XIANG; Zhimin HAO; Pangen CUI; Wenkai ZONG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
Psoriasis is a common chronic recurrent disease in dermatology. IL-23 / Th17 axis plays a critical role in the pathogenesis of psoriasis. In psoriasis patients, the gut-microbiota-skin axis may exit. Gut microbiota dybiosis may be involved in the pathogenesis of psoriasis by inducing the intestinal mucosal barrier dysfunction, bacterial translocation, inducing excessive activation of Th17, and suppressing the differention of regulatory T cells. We reviewed the recent advances of potential relation between psoriasis and gut microbiota. Probiotics and fecal microbiota transplantation could be novel therapy for psoriasis.